BAKTERI ENTOMOPATOGEN SEBAGAI AGEN BIOKONTROL TERHADAP LARVA Spodoptera litura (F.) - Deni Zulfiana; Ni Putu Ratna Ayu Krishanti; Bramantyo Wikantyoso; Apriwi Zulfitri (BERITA BIOLOGI, 2017)
Spodoptera litura (F.) (Lepidoptera: Noctuidae) is one of the agricultural pests that attacking almost all kinds of herbaceous plants, especiallyvegetables. Insect control using entomopathogenic bacteria is an alternative strategy that is effective and has a lower environmental impact than the use of synthetic insecticides. The purpose of this research was to explore entomopathogenic bacteria that have insecticidal activity against S. litura larvae at various stages of instars. The result showed that 25% of total number of isolated bacteria have potency as entomopathogenic bacteria. Isolate Staphylococcus sciuri strain BLSP-3 and isolate Serratia sp. strain BLSP-4 showed the highest larvicidal activity against the first and second instar larvae of S. litura 83% and 86%, respectively. The activity against on the third instar larvae however was only by 40%. However, the mortality caused by both isolates was lower than that of Bacillus thuringiensis (more than 90% mortality to the first and second instars and 80 % of the third instar larvae). It is suggested that both of isolates are potential to be developed further as a biocontrol agent to control S. litura population.